2015
DOI: 10.1007/s40819-015-0032-z
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Velocity and Temperature Slip Effects on Flow of Water Based Nanofluids in Converging and Diverging Channels

Abstract: Copper (Cu) and silver (Ag) nanoparticle are added to water as a base fluid to study the effects of velocity and temperature slip on the flow between converging and diverging channels. A similarity transform has been employed to reduce the nonlinear partial differential equations to a system of nonlinear ordinary differential equations which is then solved by using two analytical schemes variational iteration and variation of parameters methods. For the sake of comparison, a numerical solution using fourth ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Sheet is being x-axis is assumed to be along the stretching sheet and y-axis is assumed to be normal to it. Under aforementioned assumptions, the equations representing conservation of mass, momentum, energy, solute and nanoparticles can be written as [21]:…”
Section: Governing Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sheet is being x-axis is assumed to be along the stretching sheet and y-axis is assumed to be normal to it. Under aforementioned assumptions, the equations representing conservation of mass, momentum, energy, solute and nanoparticles can be written as [21]:…”
Section: Governing Equationsmentioning
confidence: 99%
“…They also extended these studies to the case of nanofluids. One can easily find enough literature on convective nano fluid flows, however some of the studies are reported in [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] and references therein. Those also include some studies on nanofluid flow over a permeable stretching sheet saturated by porous medium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abbasi et al addresses the influence of slip condition on hydromagnetic‐driven peristaltic motion. The impact of wall and slip characteristics on MHD peristaltic motion of nanofluid was considered by Hayat et al Several latest investigations in this regime can be pursued through Refs …”
Section: Introductionmentioning
confidence: 99%
“…The applications of slip effect include, reduction of friction, energy conversation and mimicking biological water channels [15]. Many authors have shown significant interest to study the slip effects in different geometries for different fluids [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%